2009
DOI: 10.5194/angeo-27-3691-2009
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and rainfall variability over the Indian monsoon region: distributions, trends and coupling

Abstract: Abstract. Aerosol solar absorption over the Indian monsoon region has a potential role of modulating the monsoon circulation and rainfall distribution as suggested by recent studies based on model simulations. Prior to the onset of the monsoon, northern India is influenced by significant dust transport that constitutes the bulk of the regional aerosol loading over the Gangetic-Himalayan region. In this paper, a multi-sensor characterization of the increasing premonsoon aerosol loading over northern India, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 50 publications
6
128
0
1
Order By: Relevance
“…At the end of the dry season, before the monsoon, the concentrations were close to the annual maxima, especially in Mukteshwar. This can be attributed dust events which occur when air masses arrive from the desert areas close to the Arabian Sea, such as the Thar Desert (Gautam et al, 2009). The effect of the summer monsoon is very clear in this figure.…”
Section: General Featuresmentioning
confidence: 52%
See 2 more Smart Citations
“…At the end of the dry season, before the monsoon, the concentrations were close to the annual maxima, especially in Mukteshwar. This can be attributed dust events which occur when air masses arrive from the desert areas close to the Arabian Sea, such as the Thar Desert (Gautam et al, 2009). The effect of the summer monsoon is very clear in this figure.…”
Section: General Featuresmentioning
confidence: 52%
“…As already reported in the literature (Dey and Tripathi, 2008;Gautam et al, 2009Gautam et al, , 2011Ram et al, 2008Ram et al, , 2010, mineral dust events are frequent in the Indo Gangetic Plains and occur in the Himalayan foothills, too, during the premonsoon season. The dominance of mineral dust in the high concentration events observed here is backed by information that most of the events had a PM 2.5 /PM 10 ratio of about 0.1-0.2 indicating a dominant coarse mode from primary particles (Fig.…”
Section: High Concentration Episodes During the Monsoonmentioning
confidence: 56%
See 1 more Smart Citation
“…However, other authors have noted overall negative trends. Ramanathan et al (2005) found negative trends particularly in July up to 2000, while with data up to 2004 Gautam et al (2009) found significant declining trends from July to September over India. Meanwhile, a recent comparison of trends in four different gridded rainfall data sets for India noted area-averaged rainfall decreases since the 1950s (Bollasina et al, 2011), although with considerable spatial differences (especially in north-eastern peninsular India) and relatively few gridpoints yielding statistically significant trends.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 97%
“…In contrast, in the late monsoon (August-September) it is high, reaching 470 mm in August 2008, further reducing afterwards. Note also the great variability in the rainfall amounts between the two years, able to cause significant variations in aerosol load and properties between the two contrasting monsoon years (Gautam et al, 2009). The flow chart of the wind speed (WS) and direction is shown in Figure 3 on a seasonal basis.…”
Section: Regional and Synoptic Meteorologymentioning
confidence: 99%